AN ANALYSIS OF THE STUDENTS’ PROBLEM IN COMPREHENDING PASSIVE VOICE - Eva Santoso; Rezky Uspayanti; Marni Bawawa (Acceleration: Multidisciplinary Research Journal, 2024)
This research aims to find students' problems and the causes in comprehending passive voice. This research was conducted at SMA IT Ibnu Khaldun Merauke. The method used in this research is descriptive qualitative. Data collections used tests, questionnaires, and interviews. The test and questionnaire are used to analyze students' problems and the causes of in passive voice. Data from interviews are used to complete the questionnaire results. The results of this study found three student problems in comprehending passive voice; first, students' difficulties in determining the subject and object in the passive voice, the cause of the problem is that students have difficulty changing subject pronouns to object pronouns. Second, students' difficulty in determining verb be, the causes of the problem are students have difficulty determining verb be based on the subject (singular and plural), students have difficulty determining verb be based on tense, and students sometimes forget to add verb be. Third, students' difficulties in distinguishing past form and past participle, the causes of the problem are students' difficulties in determining regular verbs and irregular verbs, in irregular verbs students often confuse V2 and V3 and lack of mastery of English vocabulary.